Endogenizing managerial delegation: A new result under Nash bargaining and network effects - Marcella Scrimitore (Economics and Econometrics Research Institute (EERI), 2019)
We reconsider the endogenous choice of delegation to a manager by two down-stream firms in both a Cournot and a Bertrand vertical market with network effects. An upstream monopolist charges a two-part tariff for a crucial input. By applying the Nash solution in a centralized bargaining, we show that hiring a manager is never an equilibrium under Cournot, regardless of network effects, while it can be the equilibrium choice for firms competing à la Bertrand, depending on the interplay between the network externalities and the degree of product substitutability.
Keywords: D43; L14; L21; 330; Nash bargaining; two-part tariff; strategic delegation; network externalities